Chapter 8 Embodied scepticism Facial expression and response relevance - Clift, Rebecca (Taylor & Francis, 2024)
This chapter extends some of the observations that Goffman made on a class of vocalisations he called 'response cries' (1978) to the domain of the multi-modal by examining an embodied practice in English interaction: a particular facial expression that 1) has particular compositional features and 2) occurs in a particular sequential position. Compositionally, this expression consists of raised eyebrows and pursed lips; sequentially, it is produced in response to a claim made by a co-participant. Instances from both institutional and mundane interaction are examined here. These show participants may or may not be gazing at their co-participant; the expression is not necessarily designed to get uptake. In this respect, this facial expression resembles Goffman's 'response cries' in being produced in the presence of others, but not necessarily designed to get responses from those others. Response relevance is seen to be shaped as much by sequential position as features of composition. This facial expression is shown, when analysed in its sequential environment, to constitute an embodied display of scepticism.